The effect of financial literacy on financial inclusion, social capital, and cognition on beginner and experienced investor - Setiadi, Maria B.B.; Murhadi, Werner R.; Marciano, Deddy (Universitas Hayam Wuruk Perbanas, 2023)
This study examines how financial literacy affects financial inclusion, social capital, and cognition in stock investors. Prospective investors or investors can manage per-sonal finances in the future. This research involves many samples with cross-sectional data. This research consists of the independent variables, financial literacy, and the dependent variables consist of financial inclusion, social capital, and cognition. The dependent variable of financial inclusion consists of access, quality, usage, and welfare; social capital consists of the dimensions of collective action, bonding, bridging and trust, and cognition. The independent variable of financial literacy consists of the dimensions of skill, behavior, knowledge, and attitude. The collected respondents were taken from 165 respondents, and they were analyzed using the structural equation modeling. After processing the data, it shows that the effect of financial literacy and cognition on financial inclusion is supported, and financial literacy on social capital cognition is supported. Meanwhile, social capital towards inclusion literacy needs to be supported. Based on the results, stock investors must be more careful in choosing investment products/institutions to avoid fraud.